HYDRODYNAMIC AND BOUSSINESQ WAVE MODELING FOR THE N219 AMPHIBIOUS AIRCRAFT SEAPLANE DOCK DEVELOPMENT PLAN IN PANJANG ISLAND - Hanah Khoirunnisa; Mardi Wibowo; Wahyu Hendriyono; khusnul Setia Wardani (Majalah Ilmiah Pengkajian Industri, 2021)
The flight test of N219 Amphibious aircraft will be targeted in 2003/2024. For flight tests, these aircraft need a seaplane dock. One of the potential locations for the seaplane dock is Panjang Island at Seribu Islands. This study aims to know the characteristic of hydrodynamic and wave conditions and to determine whether Panjang Island is suitable for the seaplane dock. This study uses a modeling method with MIKE 21 FM HD-SW module and MIKE 21 Boussinesq Wave (BW) module. The bathymetry data were obtained from the Indonesian Navy Hydrographic and Oceanographic Center (Pushidrosal), tide data is generated from Tide Model Driver (TMD), wave and wind data from ECMWF. The result of surface elevation validation between hydrodynamic modeling and TMD is 92%. During the west monsoon and spring conditions, the difference in the largest and lowest current velocity is quite large (0.018-0.199 m/s), on the other hand, when the tides are in neap conditions (0.008-0.144 m/s). Meanwhile, during the east monsoon and spring conditions, the difference in the largest and lowest current velocities is quite large (0.02-0.193 m/s), on the other hand, when the tides are in neap conditions (0.008-0.146 m/s). The maximum wave height resulting from the 50-year return period waveform modeling between 1.139 - 1.474 m. Meanwhile, the significant wave heights between 0.679 - 0.741 with a significant wave period of 13.45 seconds. In general, the current and wave conditions of the two locations are suitable for the construction of the seaplane dock, except that the dominant wave heights are still above the requirements.